Predictors of 30-day readmission and resource utilization after thoracic endovascular aortic repair. (9th May 2020) - Iyengar, Amit; Goel, Nicholas J; Kelly, John J; Han, Jason; Brown, Chase R; Khurshan, Fabliha; Chen, Zehang; Desai, Nimesh D
Abstract: OBJECTIVES: The introduction and expansion of thoracic endovascular aortic repair (TEVAR) have revolutionized the treatment of a variety of thoracic aortic diseases. We sought to evaluate the incidence, causes, predictors and costs associated with 30-day readmission after TEVAR in a nationally representative cohort. METHODS: Adult patients undergoing isolated TEVAR were identified in the National Readmissions Database from 2010 to 2014. Hospital costs were estimated by converting individual hospital charge data adjusted to 2014 consumer price indices. Multivariable logistic regression was utilized to determine hospital- and patient-level factors associated with readmissions. RESULTS: A total of 24 983 TEVARs were noted during the study period; the average age of the patients was 65 ± 16 years; 40% were women. The most common indication was an intact thoracic aneurysm (43.5%), followed by aortic dissection (30.5%). The average cost of the index admission was 63 644 ± 52 312; the average hospital stay was 11 ± 14 days; the index mortality rate was 6.7%. Readmissions within 30 days occurred in 17.4% of patients. Indications for readmission were varied; the most common aetiologies were cardiac (17.8%), infectious (16.0%) and pulmonary (12.1%). On multivariable analysis, the strongest predictor of readmission was the diagnosis, with a ruptured thoraco-abdominal aneurysm having the highest readmission burden (adjusted odds ratio 2.23, 1.17–4.24; P = 0.015). Notably, hospital volume did not predict index hospital length of stay, costs or 30-day readmissions (all P > 0.10). CONCLUSIONS: Annual TEVAR volume was not associated with any of the outcomes assessed. Rather, indication for TEVAR was the strongest predictor for many outcomes. As TEVAR becomes increasingly utilized, a focus on cardiac and vascular diseases may reduce readmissions and improve quality of care.